Constraints Faced by Pineapple Farmers in Adopting Climate Smart Adaptation Strategies in Kerala - Anil Kumar Maya, Megha; Siva, SMITHA; Thomas, Allan (Indian Journal of Extension Education, 2025)
This study investigates the challenges faced by pineapple farmers in Kerala in adopting climate-smart adaptation strategies, focusing on the districts of Ernakulam, Kottayam, and Kollam. A sample of 130 farmers was surveyed through personal interviews, and the data was analyzed using Garrett's ranking technique to prioritize the constraints hindering their adoption of climate-resilient practices. The analysis revealed that market price fluctuations, driven by reduced fruit weight due to adverse climate conditions, represent the most significant challenge. Inadequate labor availability and insufficient government support also ranked as critical barriers. Other key constraints include the high cost of agricultural inputs, lack of agricultural subsidies, limited access to climate-smart technologies, and inadequate credit facilities. The study emphasizes the urgent need for improved marketing infrastructure, enhanced labor availability, stronger government intervention, and better access to climate-smart technologies and financial resources. Addressing these barriers is essential to strengthening the adaptive capacity of pineapple farmers in Kerala, ensuring long-term sustainability and resilience in the face of climate change.